The Californios : a history, 1769-1890 - Janin, Hunt, 1940-; Carlson, Ursula, 1943- (McFarland & Company, Inc., Publishers, 2017)
"Before the Gold Rush of 1848-1858, Alta (Upper) California was an isolated cattle frontier--and home to a colorful group of Spanish speaking, non-indigenous people known as Californios. Many traces of their culture remain in California. Drawing on firsthand contemporary accounts, the authors chronicle the rise and fall of Californio men and women"--